Preliminary Physicochemical Analysis of Habb e Rasaut - Wanoo, M.I.R.; Fahamiya, N.; Shiffa, M.S.M. (Faculty of Indigenous Medicine, University of Colombo, 2025)
Habb e Rasaut is a poly-herbal Unani formulation mentioned in the National Formulary of Unani Medicine (Part V) to treat hemorrhoids and has three ingredients: Poste Haleela Zard (Terminalia chebula Retz.), Rasaut (Berberis aristata DC.), and Mukil (Commiphora mukul). However, Berberis aristata DC is not widely available in Sri Lanka, and in most instances, in its place, Coscinium fenestratum is commonly used in medicinal preparation, as both are closely resembling each other in their action and chemical constituents. Considering the above facts and the effectiveness of Habb e Rasaut, as its actions are well-matched to treat hemorrhoids, the aim of the study is to establish a quality standard of Habb e Rasaut by performing preliminary physicochemical analysis utilizing Coscinium fenestratum instead of Berberis aristata. Physiochemical evaluation was carried out according to WHO guidelines for quality control for herbal medicine. The results of physicochemical analysis of Habb e Rasaut, such as moisture content (7.5%), showed good stability, so the tablets can be stored for a long time without spoilage. The total ash value (10%) confirms the presence of natural minerals and ensures there are no harmful contaminants. The aqueous extractive value (7.5%) indicates the presence of important medicinal compounds, while the pH (4.44) shows the tablets are slightly acidic in nature. The hardness test exhibited (approximately 370 N) that the tablets are strong and not easily broken, and the friability test confirmed they can handle and transport without crumbling. The disintegration test showed that the tablets dissolve slowly, which might make them suitable for controlled-release purposes, but it took more than 01 hour. Hence, it is advisable to add a suitable disintegrating agent to modify this drug. Further, the results of this study could be utilized as a standard reference for the Habb e Rasaut formulated with Coscinium fenestratum.
Keywords: Habb e Rasaut; Berberis aristata DC; Coscinium fenestratum; Terminalia chebula Retz.; Commiphora mukul